Lignocellulose-Based Bioproducts - Karimi, Keikhosro; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume provides the technical information required for the production of biofuels and chemicals from lignocellulosic biomass. It starts with a brief overview of the importance, applications, and production processes of different lignocellulosic products. Further chapters review the perspectives of waste-based biofuels and biochemicals; the pretreatment of lignocellulosic biomass for biofuel production; cellulolytic enzyme systems for the hydrolysis of lignocelluloses; and basic and applied aspects of the production of bioethanol, biogas, biohydrogen, and biobutanol from lignocelluloses. This book is recommended for researchers and engineers and particularly students taking biofuel courses at graduate level.
Introduction to lignocellulose-based products -- Perspective of biofuels from wastes -- Pretreatment of lignocellulosic biomass -- Enzymatic hydrolysis technologies for the production of biofuels -- Bioethanol from lignocellulosic wastes: current status and future prospects -- Biogas from lignocellulosic materials -- Biohydrogen from lignocellulosic wastes -- Biobutanol from lignocellulosic wastes.
Keywords: Energy; Renewable energy resources; Biochemical engineering; Renewable energy sources; Alternate energy sources; Green energy industries; Energy; Renewable and Green Energy; Biochemical Engineering; Renewable and Green Energy; Electronic books